Hubungan Status Gizi Dengan Lama Menstruasi Pada Remaja Putri Di Kota Yogyakarta - Bima Suryantara; Gunarmi; Eka Vicky Yulivantina (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
During adolescence, nutritional needs need special attention because duringadolescence there is a physiological growth and development of organs. Growth inadolescence affects the needs, absorption, and use of nutrients, this is accompaniedby rapid enlargement of organs and body tissues. Hormonal changes duringadolescence also cause many physiological changes that affect nutritional needs inadolescents. Nutritional status affects menstruation mainly through the provision ofmaterials to make the endometrial lining again and its effect on female hormonelevels. The purpose of this study was to determine the relationship betweennutritional status and duration of menstruation in adolescent girls. This study uses aquantitative correlation method with a cross sectional time approach. Sampling withtotal sampling technique with a sample of 62 young women. The results of theanalysis using the chi square test showed that there was no relationship betweennutritional status and the length of menstruation in adolescent girls in the city ofYogyakarta, which was indicated by the p value = 0.831. Keywords: nutritional status, duration of menstruation.